ILRI's programme on animal genetic resources and potential areas of collaboration with ICARDA - Rege, J.E.O. (1999)
The article discusses the collaboration of ILRI's programme on animal genetic resources with ICARDA. It highlights the potential areas of research methods as: i. Potential areas of collaboration with ICARDA; ii. Methodologies; iii. Outputs; iRelated activities.